1990
DOI: 10.1101/gad.4.5.764
|View full text |Cite
|
Sign up to set email alerts
|

Sequences 5' to the polyadenylation signal mediate differential poly(A) site use in hepatitis B viruses.

Abstract: Most genetic elements that employ reverse transcription generate a terminally redundant genomic RNA that serves as the template for this reaction. Because the identical polyadenylation signal is present in each terminally redundant segment, synthesis of this RNA requires that this signal be ignored on the first pass of the transcription machinery, then recognized and used on the second pass. We have studied the mechanism of this differential poly(A) site use in one family of retroid elements, the hepatitis B v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
119
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 55 publications
9
119
1
Order By: Relevance
“…In addition to the AAUAAA motif and the downstream GU-rich or U-rich element of mammalian systems, upstream sequences that contribute to the efficiency of mRNA 3Ј end formation were also identified in the mammalian viruses simian virus 40 (6,36), adenovirus (8,9), hepatitis B virus (29), and human immunodeficiency virus type 1 (3,11,12,38,39). These elements function in an orientation-and position-dependent manner, and several appear to be functionally analogous.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the AAUAAA motif and the downstream GU-rich or U-rich element of mammalian systems, upstream sequences that contribute to the efficiency of mRNA 3Ј end formation were also identified in the mammalian viruses simian virus 40 (6,36), adenovirus (8,9), hepatitis B virus (29), and human immunodeficiency virus type 1 (3,11,12,38,39). These elements function in an orientation-and position-dependent manner, and several appear to be functionally analogous.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrate systems, it has been shown that an AATAAA and a downstream element are the only necessary requirements for efficient processing and that the polyadenylation site is usually at an A residue (Kessler et al 1986;Levitt et al 1989). However, upstream elements in addition to the downstream element have been described for the SV40 late poly (A) signal (Carswell and Alwine 1989), for the adenovirus late transcription unit (DeZasso and Imperiale 1989), and for the hepatitis B virus (Russnak and Ganem 1990). In most cases, the upstream element induces the recognition of weak poly( A) signals, thereby allowing a tight regulation of mRNA 3'-end formation.…”
Section: Discussionmentioning
confidence: 99%
“…Both the AATAAA and the downstream element are required for formation of the specific cleavage and polyadenylation complexes (Skolnik-David et al 1987;Gilmartin and Nevins 1989). Additional upstream sequences were shown to improve recognition of the SV40 late poly(A) signal (Carswell and Alwine 1989) and the hepatitis B virus poly(A) signal (Russnak and Ganem 1990) and to influence poly(A) site selection in the adenovirus late transcription unit (DeZasso and Imperiale 1989).…”
mentioning
confidence: 99%
“…The deviant nature of the HBV poly(A) signal might be important in this process (33). Indeed, in vitro studies designed to determine the relationship between the sequence of the poly(A) signal and its activity have classified the HBV type of poly(A) signal sequence (TATAAA) as a poor one because it supports RNA processing with only 17% efficiency (39).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in spite of its remarkable inefficiency some viruses tend to prefer this deviant poly(A) signal. These include all the mammal hepadnaviruses (33), the figwart mosaic virus (34), and Epstein-Barr virus (40). Particularly puzzling is the fact that this deviant box is conserved among the different members of mammalian hepadnaviruses, raising an interesting possibility that it has a unique but yet-unidentified role.…”
mentioning
confidence: 99%